Global Health Research Trends: a Bibliometric Review - Erlinawati, Noor Diah (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Global health is in the spotlight as the complexity of health challenges crosses national boundaries. A bibliometric study of global health research trends provides in-depth insights into the evolution, focus and impact of research in achieving a holistic understanding of global health issues. This study aims to analyze global health research trends through a bibliometric approach. The focus was on identifying key themes, patterns of collaboration between countries, the development of scientific publications, and the most cited sources of knowledge in the global health literature. Using bibliometric techniques, this study analyzed scientific publication data from various journal databases and citation indices. Keyword usage, collaboration networks between researchers, and trends in scientific publications were thoroughly analyzed to illustrate the development of global health research. The analysis highlighted dominant research themes in global health such as infectious disease epidemiology, public health, technological innovation in health care, and environmental impacts on health. Collaboration among researchers is widespread among countries, with some developed countries playing a key role. Trends in scientific publications have shown significant growth in recent years. It is concluded that this bibliometric study provides a deeper understanding of the dynamics of global health research. Cross-border collaboration and focus on crucial topics play a key role in addressing global health challenges. This analysis can serve as an important foundation to direct future research and intervention efforts that are more effective in supporting holistic global health.